A narrative review of barriers to and promotion strategies for female college students’ sports participation in a cross-cultural context - Zhou, Jiajin; Liu, Chuchen (Frontiers in Public Health, 2025)
Female university students face significant barriers to sports participation across diverse cultural contexts, despite its well-documented benefits for physical and mental health. Through a narrative review of 18 studies, this paper synthesizes barriers and identifies multi-level promotion strategies. Findings reveal four interconnected dimensions of obstacles: (a) Physiological barriers, including menstrual health concerns and heightened injury risks due to inadequate skills/knowledge; (b) Psychological barriers, characterized by body image anxiety, low self-efficacy, and trauma from negative past experiences; (c) Sociocultural barriers, manifesting as gendered stereotypes, lack of social support, and religious-cultural norms restricting participation (e.g., modesty requirements); and (d) Environmental barriers, encompassing male-dominated facilities, unsafe/inaccessible spaces, and climate-related discomfort. To address these challenges, the review proposes integrated interventions: (a) Physiological strategies include cycle-adapted exercise plans and injury-prevention education; (b) Psychological strategies focus on trauma-informed cognitive restructuring and graduated achievement systems; (c) Sociocultural strategies involve deconstructing gender biases through media representation and creating faith-sensitive spaces (e.g., women-only facilities with visual isolation); (d) Environmental strategies prioritize gender-responsive spatial redesign (e.g., reserved time slots, repurposed underutilized areas). This promotes female college students’ enthusiasm for sports participation and even encourages them to reconstruct the socio-cultural pressures they face.